Interfaces da mediação: a resistência de juízes e advogados e a mediação como parceira da jurisdição contenciosa. - Vasconcellos, Maria Paula Latache Ribeiro de (2020)
The reform of the judiciary was considered by the National Council of Justice as the new social policy, to organize and solidify at national level other mechanisms for conflict resolution, especially non-adversaries such as mediation. It is intended to address its interfaces: the resistant posture of a considerable part of the magistrates and even lawyers, contrary to the institute, and on the other hand, this same institute as a partner to the jurisdiction with a view to its essence in the Brazilian Civil Procedure. The method chosen for this research was the hypothetical-deductive, in which a review of the literature on the subject was performed. Present in both the Mediation Law and the New Code of Civil Procedure, mediation, although today an obligation established by CNJ Resolution 125/2010 within the Judiciary, has been resisted by some magistrates. and lawyers, including being confused with other traditional procedural acts. However, at the local level, from the description and analysis of productivity of the FACOL Legal Practice Center, it presents positive and motivational results of the number of agreements made through the methods of conflict resolution brought by the current Code of Civil Procedure, 2015. It can be seen that the agreements made through mediation have been growing in recent times, either in the context of a judicial process or in extrajudicial procedure, bringing the question of certainty and security generated by the Judiciary, more quickly, efficiently and effectively. partnership.